Concomitant downregulation of neuropeptide genes in a marine snail with consecutive sexual maturation after a nuclear disaster in Japan - Morishita, Fumihiro; Horiguchi, Toshihiro; Akuta, Hiroto; Ueki, Tatsuya; Imamura, Takuya (Frontiers in Endocrinology, 2023)
Consecutive sexual maturation (CSM), an abnormal reproductive phenomenon of a marine snail, Reishia clavigera, has occurred since 2017 in the vicinity of the Fukushima Daiichi Nuclear Power Plant after the nuclear disaster there. We hypothesized that alterations in animal physiology mediated through genetic/epigenetic changes could sensitively reflect environmental pollution. Understanding the mechanism of this rapid biological response should enable us to quantitatively evaluate long-lasting effects of the nuclear disaster. To determine the molecular basis for CSM, we conducted transcriptome profiling in the ganglia of normal and CSM snails. We assembled the short-read cDNA sequences obtained by Illumina sequencing, and succeeded in characterizing more than 60,000 gene models that include 88 kinds of neuropeptide precursors by BLAST search and experimental curation. GO-enrichment analysis of the differentially expressed genes demonstrated that severe downregulation of neuropeptide-related genes occurred concomitantly with CSM. In particular, significant decreases of the transcripts of 37 genes among 88 neuropeptide precursor genes, including those for myomodulin, PentaFVamide, maturation-associated peptide-5A and conopressin, were commonly observed in female and male CSM snails. By contrast, microseminoprotein precursor was the only exceptional case where the expression was increased in CSM snails. These results indicate that down-regulation of neuropeptide precursors is a remarkable feature of CSM. We also found that factors involved in epigenetic modification rather than transcription factors showed altered patterns of expression upon CSM. Comprehensive expression panels of snail neuropeptide precursors made in this study will be useful tools for environmental assessment as well as for studying marine reproductive biology.